The Utilization of Digital Technology in Population Administration Services in Mojokerto Regency - Karyn Margaretha; Diana Hertati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Population and Civil Registration Office of Mojokerto Regency as a leading sector facing various challenges in population administration services that have not been optimal has optimized by utilizing digital technology in the form of a website-based application, namely POS KETANMU or Online Service of Population System Without Meeting. This research aims to find out and describe the optimization of population administration services through the POS KETANMU website-based application. The type of research used in this research is qualitative descriptive. The data in this study was collected through observations, interviews, and documentation that were analyzed through the stages of data collection, condensation, presentation, and concluded. The results of this study show that the implementation of the POS KETANMU website-based application optimization is said to be optimal because from the use of the three optimization elements, there is only one element that has not been running optimally, namely limited resources where limitations are found such as the condition of the old computer unit and often problematic as well as the limited number of internet network devices due to the large number of use. This study also gives an evaluation because although there are still limitations in service support technology, it does not have the potential to stop the process of providing services but it is still necessary to be improved.